Application Of Special Formula NPK FERTILIZER And Compost To Increasing Cocoa (Theobroma cacao L.) Production And Productivity - Muhtar Muhtar (Syntax Corporation, 2022)
This research is aimed to analyze effect of special formula NPK fertilizer and compost doses to increasing cocoa production and productivity. This research was conducted in Cendana Hijau, Wotu, East Luwu, South Sulawesi on February until August 2021. This research was conducted by experiment using Split Plot Design with 3 replications. Main plots are compost doses consist of 3 levels, namely without compost (k0), 2,5 kg/tree dose (k1), and 5 kg/tree dose (k2). And sub plots are special formula NPK fertilizer consist of 5 levels, namely without NPK fertilizer (p0), 200 kg/ha special formula NPK fertilizer (p1), 400 kg/ha special formula NPK fertilizer (p2), 600 kg/ha special formula NPK fertilizer (p3), and 400 kg/ha NPK Phonska (p4). The result of this research showed that 5 kg/tree compost contributed highest avarage, especially number of pod harvested (29.13 pods) and beans per pod (36.52 beans). Special formula NPK fertilizer 600 kg/ha contributed the highest number of pod harvested (30.26 pods) and beans per pod (33.53 beans). Compost at dose 5 kg/tree and special formula NPK 600 kg/ha contributed highest average of dry weight beans per pods (70.77 g), dry weight of 100 beans (190.5 g), pod index (12.6), dry bean production per tree (2.33 g), and dry bean production per hectare (1.94 ton/ha).